PROBLEM-BASED LEARNING MODEL ON LEARNING OUTCOMES: QUASI EXPERIMENTAL STUDY - Kazwaini, Kazwaini; Khairan, Khairan (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2024)
This research aims to determine the influence of the Problem Based Learning model on student learning outcomes on the sub-theme of energy resource wealth in Indonesia. This research uses a 2 group quasi-experimental design. The subjects of this research were students in class IV A and IV B, consisting of 78 students. The research results show that there is a significant influence of the Problem Based Learning model on learning outcomes for the sub-theme of energy resource wealth in Indonesia. The N-Gain result in the experimental class was 74, while in the control class it was 53. With the results of hypothesis testing, H0 was rejected and Ha was accepted because tcount (3.93258) ttable (1.99167). Based on the research that has been carried out, it can be concluded that there is an influence on learning outcomes for the sub-theme of energy resource wealth in Indonesia through the Problem Based Learning modelostly in accordance with the standards. From these results, recommendations emerged that could be considered for the desired program.